A Comparative Study of Digital Financial Awareness among Gen-Y and Gen-Z (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
India has witnessed a rapid growth in digital  technologies over the past decade, with a large  percentage of the population now accessing the  internet through mobile devices. The trend of  using digital mode of finance is now gradually  shifting towards the vision of a purely virtual  banking experience. Undertaking financial  services virtually has now become a common  phenomenon and the financial habits and  consumption pattern of financial services has  now taken a paradigm shift from traditional  to virtual. Digital awareness has become an  increasingly important affair, particularly  between Generation-Y and Generation-Z.  Although both generations have grown up with  digital technologies at their fingertips, there are  significant differences in their digital awareness  and how they use digital financial services. This  research has explored the difference in level  of digital financial awareness between Gen-Y  and Gen-Z. Their consumption pattern and  financial habits have been understood through  collection of primary data through a structured  questionnaire. The awareness level of the  respondents of Gen-Y and Gen-Z has been  compared based on their gender and age. For  analyzing the data, frequency and percentage  has been evaluated of the demographic profile  and other variables. Hypothesis has been tested  through the use of t-test and ANOVA applied  through SPSS 20.
Keywords: Digital finance; Gen Y; Gen Z; awareness